Mindfulness for the self‐management of negative coping, rumination and fears of compassion in people with cancer: An exploratory study - Sian Williams; Seraphine Clarke; Trudi Edginton (Cancer Reports, 2023)
Abstract Background Cancer and its treatments have the potential to significantly impact mental health, provoking feelings of anxiety, depression, and distress, which can last long after treatment is over. One of the most rapidly emerging influences in the healthcare field is mindfulness‐based interventions (MBIs), which are designed to cultivate present moment awareness, attentional flexibility, compassion and acceptance, to reduce physical and psychological distress. However, there is limited research into the efficacy of MBIs or disease specific MBIs in shifting negative coping, ruminative thinking and fears of compassion as primary outcomes in individuals with cancer. Aims This exploratory study was designed to evaluate inter‐ and intra‐individual change in the management of negative coping, rumination and fears of compassion, following a cancer‐specific mindfulness‐based intervention. Methods and Results A single group, non‐experimental, repeated measures study of 22 participants across six cancer care centres explored the efficacy of an 8‐week Mindfulness‐Based Cognitive Therapy for Cancer (MBCT‐Ca) course. The Reliable Change Index (RCI) examined reliable clinical improvement, deterioration, or no change in individuals on the Mental Adjustment to Cancer Scale (MACS), the Ruminative Responses Scale (RRS) and the Fears of Compassion Scale (FCS). About 82% of participants (n = 18) saw an improvement in at least one measure. A significant decrease in primary outcome scores was observed in negative coping, ruminating and fears of self‐compassion. There were significant correlations between the fear of self‐compassion and depressive ruminating, fear of accepting compassion from others and showing it to others pre and post intervention. Conclusion Our findings indicate that the MBCT‐Ca programme may significantly reduce negative coping, ruminating and fears of self‐compassion improving psychological health and wellbeing in cancer survivors.